The benefits of long-duration energy storage for New England’s energy system decarbonization goals - Sergio Freeman; Ertan Agar (Next Energy)
Utilizing a macro-scale energy model alongside 44 years of New England’s hourly weather data from MERRA-2, this study investigates the benefits of various combinations of renewable energy technologies, particularly wind and solar, and their integration with long-duration energy storage (LDES) systems. The potential of these renewable energy sources to enhance both the reliability and affordability of New England’s power system is evaluated. The findings demonstrate that incorporating LDES into the technology mix leads to a remarkable 55% reduction in overall system costs compared to relying solely on short-duration energy storage (SDES), such as lithium-ion batteries. Additionally, the cost reductions of LDES lead to approximately a 35% increase in the utilization of solar generation. The results suggest that total system costs for LDES are more responsive to relative decreases in power-capacity costs than decreases in energy-capacity costs. Furthermore, the analysis indicates that a combination of different LDES storage technologies can offer the most cost-effective solution for wind-solar power systems. Overall, by examining the interplay between different storage technologies and their impact on system costs, this research contributes significantly to the discourse on sustainable energy solutions.